Pengembangan Lembar Kerja Siswa Model ELPSA pada Materi Matriks - Indri Rahayu; Dian Mayasari; Sadrack Luden Pagiling (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2021)
This study aims to produce a valid, practical, and effective ELPSA (Experiences, Language, Picture, Symbol, Applications) learning tool of matrix content. Research method using ADDIE model. The media tested at one of the vocational high schools in Merauke Regency. Validation sheets measure the validity of student worksheets and lesson plans assessed by the three validators. The practicality of the worksheet is measured by student responses questionnaires and learning implementation observation sheets. The effectiveness was measured by pretest and post-test. The result of this study showed that the validity of the lesson plan was 54% and 28%, the validity of the students’ worksheets was 63% and 27%. The validity of the pretest was 59%, and post-test sheets were 23%. The practicality value obtained from the student response questionnaire was 75%. Teacher and student activities in the learning process meet the excellent category. On the effectiveness test, all students did not satisfy the minimum class criteria at the pretest with an average score of 23.70. In the post-test results, all students passed with an average score of 84.20. After learning by the ELPSA model, student mathematics achievement increased by 100%. It can be concluded that the ELPSA model learning tool has met the valid, practical, and effective criteria to suit classroom learning.